Pengaruh lingkungan kerja dan motivasi kerja terhadap kinerja pegawai Dinas Pemberdayaan Masyarakat dan Desa (DPMD) Kota Trenggalek - Muhamad Abid; Kamaludin Irqas (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
The purpose of this study was to determine partially the effect of the work environment on the performance of employees of the Trenggalek City Community and Village Empowerment Service (DPMD). To find out partially the effect of motivation on the performance of employees of the Trenggalek City Community and Village Empowerment Service (DPMD), and to know simultaneously the effect of the Work Environment and Motivation together on the performance of the employees of the Trenggalek City Community and Village Empowerment Service (DPMD). This research method uses a descriptive type with a quantitative approach. The analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, correlation test, multiple linear regression test, determination test and significant test (t test and f test). The results showed that partially the work environment has a positive effect on employee performance, this can be seen from the t-test with a t-value of 6.616 > 1.665 with a significance level of 0.000 this value is smaller than 0.5 (0.000 < 0.5). Partially, work motivation has a positive effect on employee performance, this can be seen from the t test with a t-value of 5.642 > 1.665 with a significance level of 0.000 this value is greater than 0.5 (0.000 < 0.5). And Simultaneously the work environment and work motivation have a positive and significant effect on employee performance, this can be seen from the results of the F test with Fcount 29.416 and Ftable 3.10 (29.416 > 3.10). Thus it can be interpreted that the work environment and work motivation simultaneously have a significant influence on employee performance.